KEBIJAKAN PEMANFAATAN APLIKASI BRIMO UNTUK MENINGKATKAN KUALITAS PELAYANAN (Studi Kasus BRI Unit Sungai Lulut) - Siska Emillia; M. Zainul; Prihatini Ade Mayvita (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to find out: (1) How is the policy of using the BRIMOapplication in improving service quality, (2) What are the obstacles or challengesfaced by Bank BRI Sungai Lulut Unit in realizing the policy of using the BRIMOapplication to improve service quality to customers, (3) What are the efforts made toovercome obstacles in the implementation of the policy on the use of the Brimoapplication to improve service quality,(4) How are the customer responses of BRI Sungai Lulut Unit regarding the policy ofusing the BRIMO application in serving their customers.This type of research is descriptive qualitative research. Research resourcepersons are employees of BRI Sungai Lulut Unit and BRI Customers of Sungai LulutUnit. Data analysis technique using Miles & Huberman.The results of the study show that the policies made by BRI can improve thequality of service, the obstacles faced in introducing the BRIMO service applicationso far do not exist, because the only problem is customers who do not have asupporting gadget and an unstable network. helped by the BRIMO applicationbecause they can transact faster, easier and do not need to go to a bank or ATManymore. There are 5 indicators of service quality, namely: (1) Reality, makes it veryeasy for customers to transact. To transact through BRIMO, not all transactions aresubject to admin fees, BRI employees at Sungai Lulut Unit work according to SOPsset by BRI in a precise, reliable, accurate, and reliable manner. solve customerproblems and can solve them personally. (2) Assurance, employees of BRI SungaiLulut Unit are always polite, courteous, provide good and correct knowledge andalso create a sense of trust and confidence in customers. (3) Tangible, BRI SungaiLulut unit has a comfortable, cool room, the employees are neat and clean. For theBRIMO application, it is quite complete and looks easy and clear to understand. (4)Empathy, always providing the latest information to customers when providingservices directly, also posting status on social media in the form of photos and videos,in the BRIMO application there is always the latest information. (5) Responsiveness,Customer Service BRI Sungai Lulut Unit in resolving customer problems quickly andwell. Now if a problem occurs, it can be reported directly through the BRIMOapplication without having to come to the bank.